Implementasi Augmented Reality Pengenalan Perangkat Komputer Menggunakan Metode Prototype (Studi Kasus : SMK Excellent 1 Tangerang) - Nurul Badri; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2023)
The world of education uses augmented reality technology itself is still a little use. Augmented reality (AR) is a technology that combines two-dimensional or three-dimensional virtual objects into a real three dimensional environment and then projects these virtual objects in real time. Augmented Reality-based applications with marker-based tracking techniques become a solution in practicing computer equipment at SMK Excellent 1 Tangerang, especially for class 10 TKJ to users, both for teachers and students. The concept of this application is the introduction of computer devices at SMK Excellent 1 Tangerang through the camera installed on the user's smartphone. by pointing the smartphone camera at the marker the user will get information about the desired computer device. for example, the user points the smartphone camera at the marker, then the user will get information on a 3D computer device object, description, function on each object, users can also take quizzes on the application in the form of 2D image questions in the introduction of computer devices so that student learning will be more interesting and interesting. interactive in the introduction of computer devices.